Establishing Medical Education Unit (MEU) and Medical Skill Centre (MSC) at Medical Institutes is the Demand of Present Time (Bangladesh Journal of Physiology and Pharmacology, 2014)
DOI: http://dx.doi.org/10.3329/bjpp.v27i1-2.20071 Bangladesh J Physiol Pharmacol 2011; 27(1&2):28-30